Isolation, Screening and Optimization of Estuary Region (Khambhat, Gujarat) Microalgae for Lipid/Oil Production - Guruvaiah, Mahendraperumal; Narra, Madhuri; Dixit, Garima; Karawadia, Punit; Shah, Deval (International Journal of Applied Sciences and Biotechnology, 2015)
Water and soil samples were collected from gulf of Khambhat region, Gujarat. The cations and anions like calcium, chloride, fluoride, magnesium, sulphate and total hardness as calcium carbonate were analyzed. Collected estuarine samples were cultured in three different media under standard laboratory conditions. These enrichments were then used to isolate pure unialgal culture by conventional method. Thirty four isolates belonging to twelve species of Cyanobacteria, twenty species of Chlorophyta and two taxa of Bacillariophyta were identified and are maintained at SPRERI centre. The Chlorophyta were found better accumulators of lipids than the cyanobacterial species. Five promising strains (SBC 7, SBC 9, SBC 17, SBC 18 and SBC 19) have been selected. In-house isolates SBC19 and SBC 17 showed highest acetyl CoA carboxylase (ACCase) of 55.2 (U/ml) and 51.2 (U/ml) respectively, with 0.375 g l-1 nitrogen concentration in 24 days. Biomass production was highest for 2.4 g/l, (SBC 19) and 2.7 g/l (SBC 17) with 1.5 g l-1 nitrogen concentration. The highest lipid content was 52% and 48% in SBC19 and SBC 17, respectively, with 0.375 g l-1 nitrogen concentration of solvent extraction method. Lipid accumulation was found enhanced by more than 50% on dry mass basis under nitrogen starvation. Int J Appl Sci Biotechnol, Vol 3(2): 197-201 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12534